2008
DOI: 10.1159/000130416
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Drinking in Young Adults: The Predictive Value of Personality when Peers Come Around

Abstract: This study examined whether personality traits and peer drinking affect alcohol consumption in young adults. Data were analyzed from a study that was conducted in a ‘bar laboratory’ in which ad-lib drinking of peer groups was observed. The findings indicate that extroversion is moderately associated with self-reported daily drinking, while low emotional stability is modestly associated with alcohol-related problems. With regard to drinking in the observational drinking setting, personality is not associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 89 publications
1
15
1
2
Order By: Relevance
“…Their lack of trust may also lead them to disregard public health messages about the dangers of illicit drug use. Those who are high in Agreeableness, in contrast, tend to be rule followers and are more likely to conform to social norms than their more antagonistic peers (Van Schoor et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Their lack of trust may also lead them to disregard public health messages about the dangers of illicit drug use. Those who are high in Agreeableness, in contrast, tend to be rule followers and are more likely to conform to social norms than their more antagonistic peers (Van Schoor et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Kairouz et al (2002) sampled drinking occasions through a retrospective survey among college students and found that various reasons for drinking, such as to be sociable, to conform with others, to feel good, or to forget worries (all compared to drinking to enjoy the taste or to enhance a meal) increased alcohol use, as did a larger drinking group size. Another study found that college students scoring high on the agreeableness personality trait adapted their drinking behavior more easily to a high- or low-drinking peer group in a bar-laboratory setting than those who scored low on agreeableness (van Schoor et al 2008). In another study of drinking among college students, the time spent with friends was positively associated with alcohol use, as reported in daily assessments (Mohr et al 2005), while enhancement motives moderated this association.…”
Section: Interactions Between Drinking Motives and The Drinking Groupmentioning
confidence: 99%
“…The SDM provides a promising framework for investigating young adult problems because it incorporates empirically determined risk and protective factors across multiple life domains. The focus of the SDM on social influences may be especially apt for this period during which the alcohol-related norms and behaviors of peers and social networks have been found to be particularly important, both for both college and non-college young adults (Lau-Barraco & Collins, 2011; Overbeek et al, 2011; Talbott, Moore, & Usdan, 2012; van Schoor, Bot, & Engels, 2008; White, Fleming, Kim, Catalano, & McMorris, 2008). Here we extend the SDM into the mid 20s in order to investigate hypothesized social developmental processes in young adulthood and their relationship to later AUD symptoms.…”
Section: The Social Development Modelmentioning
confidence: 99%